1995
DOI: 10.1042/bj3080237
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of carbohydrate binding by a 14 kDa S-type mammalian lectin

Abstract: The thermodynamics of the binding of derivatives of galactose and lactose to a 14 kDa beta-galactoside-binding lectin (L-14) from sheep spleen has been studied in 10 nM phosphate/150 mM NaCl/10 mM beta-mercaptoethanol buffer, pH 7.4, and in the temperature range 285-300 K using titration calorimetry. The single-site binding constants of various sugars for the lectin were in the following order: N-acetyl-lactosamine thiodigalactoside > 4-methylumbelliferyl lactoside > lactose > 4-methylumbelliferyl alpha-D-gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
3
39
0
1
Order By: Relevance
“…Observation of enthalpy-entropy compensation is not surprising as thermodynamic studies on several lectins strongly emphasize the importance of water as a mediator in proteincarbohydrate recognition (Lemieux et al, 1994;Puri and Surolia, 1994;Toone, 1994;Ramkumar et al, 1995). This fact is also succinctly brought out by the high resolution structural analysis of Lathyrus ochrus lectin I complexed with its complementary oligosaccharide ligand (Bourne et al, 1992).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Observation of enthalpy-entropy compensation is not surprising as thermodynamic studies on several lectins strongly emphasize the importance of water as a mediator in proteincarbohydrate recognition (Lemieux et al, 1994;Puri and Surolia, 1994;Toone, 1994;Ramkumar et al, 1995). This fact is also succinctly brought out by the high resolution structural analysis of Lathyrus ochrus lectin I complexed with its complementary oligosaccharide ligand (Bourne et al, 1992).…”
Section: Discussionmentioning
confidence: 86%
“…Previous investigations of the binding thermodynamics of the lectins with monosaccharides have shown that these reactions are enthalpically driven with little increase in the heat capacity change and that they exhibit enthalpy-entropy compensation (Schwarz et al, , 1993. These characteristics have also been observed for the binding of the trisaccharide methyl 3,6-di-O-(␣-D-mannopyranosyl)-␣-D-mannopyranoside to concanavalin A (Williams et al, 1992) as well as for the binding of derivatives of galactose and lactose to the 14-kDa S-type lectin from sheep spleen (Ramkumar et al, 1995).…”
mentioning
confidence: 75%
“…It is possible, however, that the second site described here is part of an extended site that possesses significant affinity only for ligands larger than a monosaccharide. Precedent for such a site is found in lectin IV of Griffonia simplicifolia, which has no significant affinity for monosaccharides but is specific for the Lewis b tetrasaccharide (46), and the galectins, which bind galactose poorly but interact strongly with lactose and lactosamine (47). It is also notable that ␣-Me-Man is bound at the second site in an orientation that would allow an oligosaccharide to extend from Ca 2ϩ -site 2 to the second site.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has also proved instrumental in obtaining inferred information on the binding-site architecture of related galectins (Solis et al, 1996). Corroborating the evidence from X-ray crystallography, site-directed mutagenesis and chemical mapping, titration calorimetry indicates that hydrogen bonding and van der Waals' interactions provide the major stabilizing forces for the complex in addition to a reorganization of water molecules (Ramkumar et al, 1995). The source of galectin-I and its primary sequence can even bring forth differences in the binding energetics, precluding premature generalization (Gupta et al, 1996 b).…”
Section: Galectinsmentioning
confidence: 99%